2015
DOI: 10.1016/j.ijfoodmicro.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Listeriaphages and coagulin C23 act synergistically to kill Listeria monocytogenes in milk under refrigeration conditions

Abstract: Bacteriophages and bacteriocins are promising biocontrol tools in food. In this work, two Listeria bacteriophages, FWLLm1 and FWLLm3, were assessed in combination with the bacteriocin coagulin C23 to inhibit Listeria monocytogenes. Preliminary results under laboratory conditions demonstrated that both antimicrobials act synergistically when they were applied in suboptimal concentrations. The combined approach was further assessed in milk contaminated with 5×10(4) CFU/ml L. monocytogenes 2000/47 and stored at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Significantly, the authors in the study concluded that the rate of development of resistance was higher when the antimicrobials were used independently, relative to the combination of the two antimicrobials together. This phenomenon of delayed resistance development could explain the synergistic effects observed in the study (Rodríguez-Rubio et al, 2015). …”
Section: Other Types Of Effective Interactions Against Pathogens Invomentioning
confidence: 64%
See 1 more Smart Citation
“…Significantly, the authors in the study concluded that the rate of development of resistance was higher when the antimicrobials were used independently, relative to the combination of the two antimicrobials together. This phenomenon of delayed resistance development could explain the synergistic effects observed in the study (Rodríguez-Rubio et al, 2015). …”
Section: Other Types Of Effective Interactions Against Pathogens Invomentioning
confidence: 64%
“…For instance, a recent study evaluated the efficacy of combinations of the class II bacteriocin coagulin C23 with listeriaphages against L. monocytogenes and found that they act in a synergistic manner against the food-borne pathogen (Rodríguez-Rubio et al, 2015). More specifically, coagulin C23 was combined with the phages FWLLm1 or FWLLm3 and synergistic effects were apparent when the two antimicrobials were mixed in sub-inhibitory concentrations.…”
Section: Other Types Of Effective Interactions Against Pathogens Invomentioning
confidence: 99%
“…Bacteriocins such as nisin have been used in meat mince to inhibit L. monocytogenes (Pawar et al 2000). Synergistic action between listeriophages and the bacteriocin coagulin C23 demonstrated inhibition of L. monocytogenes in refrigerated milk (Rodr ıguez-Rubio et al 2015). Essential oils of plant origin also have potential antimicrobial properties and can reduce Listeria survival in various products .…”
Section: Novel and Emerging Therapies To Combat Listeriosismentioning
confidence: 99%
“…Some of the components of milk can act as barriers to the interaction between the bacteriophages and the host bacteria. For example, milk proteins or fat globules may interrupt a bacteriophage’s contact with the bacterial cell surface (Rodríguez-Rubio et al , 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Bacteriophages are extensively distributed in all environments and can kill bacteria, so they naturally play a role in controlling bacterial populations (Hagens and Loessner, 2014; Rodríguez-Rubio et al, 2015). Bacteriophages are thought to be safe for humans, animals, and plants (Rodríguez-Rubio et al , 2015). Biocontrol strategies based on bacteriophages have received an increasing amount of interest owing to their efficacy, practicability, safety, and economic feasibility (Farber and Peterkin, 1991; Hagens and Loessner, 2007; Hagens and Loessner, 2010; Hagens and Offerhaus, 2008).…”
Section: Introductionmentioning
confidence: 99%